The clinical value of immune cell composition in the diagnosis of pediatric sepsis - Shen, Jie; Zhong, Qing; Su, Jing; Shen, Xuan; Li, Wenya; Sun, Tianyu; Zhang, Yaoyun; Qi, Jijin (Frontiers in Pediatrics, 2025)
BackgroundThe objective of this study was to evaluate the diagnostic significance of various immune cell ratios in children with sepsis via the analysis of clinical data.MethodsThis retrospective study analyzed clinical data admitted to the pediatric intensive care unit (PICU) of Jiangsu Province (Suqian) Hospital between January 2023 and December 2024. Receiver operating characteristic (ROC) curve analysis evaluated the diagnostic performance of peripheral blood laboratory assessments and Immune cell ratios (platelet count divided by lymphocyte count (PLR), monocyte count divided by lymphocyte count (MLR), neutrophil count divided by lymphocyte count (NLR), the ratio of neutrophils to (white blood cells—neutrophils) (dNLR), and neutrophil count multiplied by 100 divided by (lymphocyte count multiplied by platelet count) (NLPR)). Using Statistical Package for the Social Sciences (SPSS) 26.0 performed by Mann–Whitney U and Chi-square tests, with significance defined as P < 0.05.ResultWe analyzed the clinical data from 321 pediatric patients [201 sepsis (SP) and 120 healthy controls (HC)]. Compared to HC, the SP group exhibited elevated white blood cell (WBC), neutrophils, procalcitonin (PCT), platelets (PLT), and erythrocyte sedimentation rate (ESR) but reduced lymphocytes, monocytes, and hemoglobin; C-reactive protein (CRP) was significantly increased in the SP group (P < 0.001). ROC analysis identified NLR [The area under the ROC curve (AUC) = 0.932], PLR (AUC = 0.907), and NLPR (AUC = 0.848) as effective immune ratio biomarkers, while MLR (AUC = 0.784) showed limited utility. Among laboratory tests, WBC (AUC = 0.902), neutrophils (AUC = 0.919), CRP (AUC = 0.923), PLT (AUC = 0.879), and ESR (AUC = 0.875) demonstrated strong diagnostic accuracy, whereas lymphocyte, monocyte, and hemoglobin levels were less discriminative.ConclusionOur study reveals that combining immune cell ratios and CRP significantly enhances early detection of pediatric sepsis, improving clinical outcomes.